Investigation of novel evaporative cooling material for Cyprus climate - Abohorlu Doğramacı, Pervin (2018)
Energy consumption by human enhanced activities has led to distinctive environmental problems; in particular, climate change and global warming. In hot regions, the main reason for energy consumption comes from the cooling of many buildings. The intensity and duration of the sunshine in hot regions have a direct relation with the usage of cooling systems. The energy used for cooling purpose is continuously increasing and expected to increase in the following years. Evaporative cooling is one of the passive cooling method which has been used throughout history. As it is cheaper, environmentally-friendly and simpler compared to vapour compression systems, it is more widely used in residential, commercial and industrial buildings in hot and dry regions. Since this method is less efficient and limited under hot and humid climate, the desiccant based evaporative cooling system is preferred in such areas in order to dehumidify the air. The pad material used for evaporative cooling system is important as it helps to evaporate the water. Therefore, the material should be porous enough to absorb water which enhances the rate of evaporation. Moreover, the material should be available and cheap. This study shows the potential of using different materials for evaporative cooling systems. The aim of this study is to investigate the feasibility, suitability and potential of using local materials such as eucalyptus fibres, as cooling pads for evaporative cooling system in hot and dry regions. In addition to this, the liquid desiccant evaporative cooling systems by using potassium formate is also studied for hot and humid areas in Cyprus. Since Cyprus has multi-climate regions due to the topography and different weather condition, different cooling systems can be used for each region. The results are reported in terms of temperature difference, cooling output, COP, etc. The wind tunnel is used to test the eucalyptus fibres with an inlet air temperature of 35 °C to simulate the climate in Cyprus. It was found that the maximum reduction of air temperature was between 11.3 °C and 6.6 °C, while the maximum cooling efficiency was in the range of 71% and 49% at 0.1 and 0.6 m/s air velocity respectively. Corresponding cooling capacities were also calculated as 108 and 409 W indicating a directly proportional relation between air velocities and cooling performance. Following this, the conceptual design ideas of integrated eucalyptus fibres based evaporative cooling panel (EFECP) into building elements are considered to meet the demand for cooling and the architectural requirements of the building. These design ideas were developed for shutter, fenestration, toplighting elements, wind catcher-solar chimney and wall design of the building. The cooling performances of the hollow fibre integrated by using potassium formate desiccant based evaporative cooling system were experimentally investigated under the incoming air temperature in the range of 35 ˚C to 40 ˚C. The cooling capacity is increased as the air velocity is increased. At 3.5m/s, the cooling capacity is 1340 W, 1530 W and 1920 W respectively for incoming air relative humidity of 60%, 65% and 70%. Both evaporative cooling systems performances are discussed and clearly presented in this study. From the experimental testing in this thesis, it is concluded that local eucalyptus fibres can be used for hot-dry areas and liquid desiccant evaporative cooling systems can be used for hot-humid areas of Cyprus. Since using of eucalyptus fibres for evaporative cooling system is locally available, simple construction and easy to apply, the design ideas for integrating eucalyptus fibres with evaporative cooling system are developed within the scope of the thesis. The usage of local eucalyptus fibres and Polyvinylidene fluoride (PVDF) hollow fibres as evaporative cooling pad, the evaporative cooling process designed by using fibres and the conceptual building design ideas integrated local eucalyptus fibres combined with evaporative cooling system are all the novel ideas of this thesis.